Electric power systems : a first course - Mohan, Ned. (Hoboken, N.J. : John Wiley & Sons, 2012)
'Author Ned Mohan has been a leader in EES education and research for decades. His three-book series on Power Electronics focuses on three essential topics in the power sequence based on applications relevant to this age of sustainable energy such as wind turbines and hybrid electric vehicles. The three topics include power electronics, power systems and electric machines. Key features in the first Edition build on Mohan's successful MNPERE texts; his systems approach which puts dry technical detail in the context of applications; and substantial pedagogical support including PPT's, video clips, animations, clicker questions and a lab manual. It follows a top-down systems-level approach to power electronics to highlight interrelationships between these sub-fields. It's intended to cover fundamental and practical design. This book also follows a building-block approach to power electronics that allows an in-depth discussion of several important topics that are usually left. Topics are carefully sequenced to maintain continuity and interest. '--
Machine generated contents note: Chapter 1: Power Systems: A Changing Landscape Chapter 2: Review of Basic Electric Circuits and Electromagnetic Concepts Chapter 3: Electric Energy and the Environment Chapter 4: AC Transmission Lines and Underground Cables Chapter 5: Power Flow in Power System Networks Chapter 6: Transformers in Power Systems Chapter 7: High Voltage DC (HVDC) Transmission Systems Chapter 8: Distribution Systems, Loads and Power Quality Chapter 9: Synchronous Generators Chapter 10: Voltage Regulation and Stability in Power Systems Chapter 11: Transient and Dynamic Stability of Power Systems Chapter 12: Control of Interconnected Power Systems and Economic Dispatch Chapter 13: Transmission Line Faults, Relaying and Circuit Breakers Chapter 14: Transient Over-Voltages, Surge Protection and Insulation Coordination .
Includes bibliographical references and index.
Keywords: Electric power systems; TECHNOLOGY & ENGINEERING / Power Resources / General